Дослідження можливості складного кругового руху імплантатів - Ханкунь, Цзяо; Аврунін, О. Г. (Vinnytsia National Technical University, 2023)
In this paper, we explore the feasibility of controlling the circular motion of the implant in a non-contact manner by controlling the change of the external magnetic field in a magnetic stereotaxic system. The change of the external magnetic field was simulated through computer simulation experiments, so as to control the circular motion of a small permanent magnet in a non-contact manner, and in the actual experiment, the slide rail system was equipped with a large permanent magnet to form an external magnetic field, and the operation of the slide rail system was controlled by an Arduino microcontroller. The results of computer simulation experiments were verified, and the feasibility of non-contact control of the circular motion of the implant was clarified.